2020
DOI: 10.3390/ijms21030805
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in Dipeptidyl Peptidase-4 Promotes Chemoresistance Through the CXCL12/CXCR4/mTOR/TGFβ Signaling Pathway in Breast Cancer Cells

Abstract: Dipeptidyl peptidase (DPP)-4, a molecular target of DPP-4 inhibitors, which are type 2 diabetes drugs, is expressed in a variety of cell types, tissues and organs. DPP-4 has been shown to be involved in cancer biology, and we have recently shown that a DPP-4 inhibitor promoted the epithelial mesenchymal transition (EMT) in breast cancer cells. The EMT is known to associate with chemotherapy resistance via the induction of ATP-binding cassette (ABC) transporters in cancer cells. Here, we demonstrated that defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…In this article, we nd that appears MCF-7/ADR cells have more signi cant characteristics of EMT than DOX sensitive MCF-7 cells, manifested as the down-regulated of E-cadherin protein and the up-regulated of N-cadherin protein and Vimentin. In fact, Li and his colleagues also con rmed that DOX could induce EMT and apoptosis in MCF-7 cells (Li et al 2020b). The invasion and metastasis are signi cantly enhanced in tumor cells with EMT characteristics.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this article, we nd that appears MCF-7/ADR cells have more signi cant characteristics of EMT than DOX sensitive MCF-7 cells, manifested as the down-regulated of E-cadherin protein and the up-regulated of N-cadherin protein and Vimentin. In fact, Li and his colleagues also con rmed that DOX could induce EMT and apoptosis in MCF-7 cells (Li et al 2020b). The invasion and metastasis are signi cantly enhanced in tumor cells with EMT characteristics.…”
Section: Discussionmentioning
confidence: 97%
“…EMO has been found to inhibit to increase sensitivity to DOX and PTX in breast cancer (Li et al 2020b, Gu et al 2020, and inhibits EMT in triple negative breast cancer ). It's reported that solid lipid nanoparticles of EMO can signi cantly block the cell cycle and induce apoptosis of MCF-7 cells compared with free EMO (Wang et al 2012), which indicates that lipid nanoparticles delivering EMO may be a promising method for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…found that suppressed CXCL12/CXCR4 signaling pathway or silenced CXCR4 in BCSCs sensitizes BC to immune checkpoint blockers, inhibiting metastasis reversing drug-resistance in BC ( Chen I. X. et al, 2019 ). In a similar mechanism, DPP-4 inhibitors were found to reverse drug-resistance via ABC transporters-mediated CXCL12/CXCR4/mTOR/TGFβ axis in BC cells ( Li et al, 2020 ). An innovative strategy, consisting of an oncolytic virus loaded with a CXCR4 antagonist, was utilized for targeting the CXCL12/CXCR4 signaling pathway, being remarkably effective in primary and metastatic BC ( Gil et al, 2013 ).…”
Section: Central Surface Markers In Breast Cancer Stem Cellsmentioning
confidence: 99%
“…Cells undergoing EMT processes are known to induce ATP-binding cassette (ABC) transporter overexpression, which is related to cancer drug resistance in several cancer cells [ 94 , 95 ]. With regard to this, we have reported that the DPP-4 inhibitor increases ABC transporters via EMT induction, resulting in breast cancer chemoresistance ( Figure 1 ) [ 76 ]. A xenograft model of DPP-4-overexpressed epithelial ovarian cancer cells exhibited as larger bodies, but at the same time, displayed more chemosensitivity to paclitaxel [ 43 ].…”
Section: The Impact Of Dpp-4 Inhibition On Existing Tumorsmentioning
confidence: 99%
“…Furthermore, a clinical report exploring the impact of DPP-4 inhibitors on chemotherapy outcomes in diabetic patients with cancer is lacking. In previous preclinical studies, either EMT or increased CXCL12 level, the condition associated with DPP-4 inhibition, is relevant for chemoresistance [ 76 , 136 , 137 ]. DPP-4 also plays an important role in the immune system, especially T-cell functions.…”
Section: The Influence Of Dpp-4 Inhibitors On Cancer: Clinical Evidencementioning
confidence: 99%